Dynamics of exopolymeric carbon pools in relation with phytoplankton succession along the salinity gradient of a temperate estuary (France). (30th September 2018) - Morelle, Jérôme; Schapira, Mathilde; Françoise, Sylvaine; Courtay, Gaëlle; Orvain, Francis; Claquin, Pascal
Abstract: In parallel to phytoplankton community dynamics, transparent exopolymeric particles (TEP) and exopolymeric substances (EPS) were investigated along the salinity gradient of a temperate estuary (Seine estuary, Normandy, France) over the course of a year. The phytoplankton community was mainly dominated by marine diatom species (especially Skeletonema sp., Nitzschia sp., and Paralia sulcata ) associated with a spring bloom of pico-eukaryotes and the development of Cryptophyceae in summer. The decreases in species richness and salinity were correlated along the estuary and a significant exponential relationship between species richness and primary production was identified. Concentrations of TEP and EPS (soluble and bound carbohydrates) are highly dynamic in this estuary and can reach respectively 69 mgC L −1, and 33 mgC L −1 . TEP distribution was mainly related to physical factors (hydrodynamics, maximum turbidity zone formation and sediment resuspension) probably produced by stressed or dying phytoplankton, while EPS appeared to be excreted during the phytoplankton spring bloom. Soluble and bound EPS appear to be related to Skeletonema sp. and Cryptophyceae occurrences. This paper presents the dynamic pattern of these carbon pools, which play an important role in the trophic network and influence the flocculation processes involved in the fate of both organic and inorganic matter. Graphical abstract: Image 1